Characterization of the petrology of the tar sandstone rock of the Paraná basin - Rafael de Aquino Amadeu; Thiago Lynyker da Silva Bernardes; Rodrigo Sousa Santos; Rafael Henrique L. Garcia; Alexandre França Velo; Francisco Assis Cavallaro; Carlos Henrique Mesquita; Margarida Mizue Hamada (Brazilian Journal of Radiation Sciences, 2021)
In the state of São Paulo (Brazil), occurrences of tar sandstone are known in Botucatu, Angatuba, Pirambóia, Anhembi and Bofete municipalities. In the present work a sample of white tar sandstone was taken from Anhembi municipality, located at Km 168 of the Castelo Branco Highway. In the petroleum area, sandstones act as excellent hydrocarbon reservoirs, since they have specific characteristics, such as: high porosity and permeability. Porosity is a property of rocks, and it may be understood as the voids contained in the matrix (where fluids remain stored), while permeability is the ability of the rock to transmit these stored fluids. Due to these characteristics of sandstones, researchers have shown a growing interest in the study and characterization of this type of rock, which is a fundamental element of an oil system. In the present work, four characterization techniques were used in the Anhembi tar sandstone sample, namely: X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Scanning Electron Microscope (SEM) and the third generation Industrial Computerized Tomography. Through these techniques, the chemical composition, grain morphology, crystalline structure phases and an image of a slice of the internal structure of the white tar sandstone sample were obtained.